2020
DOI: 10.3390/ijms21082840
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Matrix Metalloproteinases and Their Inhibitors in Endometrium: High Levels in Endometriotic Lesions

Abstract: Endometriosis is a condition defined as presence of endometrium outside of the uterine cavity. These endometrial cells are able to attach and invade the peritoneum or ovary, thus forming respectively the deep infiltrating endometriosis (DIE) and the ovarian endometrioma (OMA), the ectopic lesions feature of this pathology. Endometriotic cells display high invasiveness and share some features of malignancy with cancer cells. Indeed, the tissue remodeling underlining lesion formation is achieved by matrix metall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…Protein–protein interaction analyses of the identified proteins have also confirmed the central position of MMP2 and TIMP1 in protein–protein interaction networks. Furthermore, TIMP1 has already been described as a protein that is secreted by endometriotic lesions 53 , and the present study supports its great value as a potential biomarker.…”
Section: Discussionsupporting
confidence: 85%
“…Protein–protein interaction analyses of the identified proteins have also confirmed the central position of MMP2 and TIMP1 in protein–protein interaction networks. Furthermore, TIMP1 has already been described as a protein that is secreted by endometriotic lesions 53 , and the present study supports its great value as a potential biomarker.…”
Section: Discussionsupporting
confidence: 85%
“…Microscopic imaging of the central core and peripheral rim of the spheroids showed that at 2 and 4 h of incubation, the PL1-AgNPs were internalized in the spheroid cells at the periphery of the spheroids To bind MMAE to AgNPs we used a valine-citrulline linker that is cathepsin B sensitive. Some ECM proteases, such as matrix metalloproteinases, are overexpressed in ectopic endometrial tissue [61,62]. It is possible that application of alternative enzyme-cleavable linkers might result in increased release of the drug in endometriotic lesions as we have shown previously in tumor mouse models [63,64].…”
Section: Pl1 Promotes the Penetration And Cytotoxicity Of Agnps In Endometriotic Spheroidsmentioning
confidence: 83%
“…Some studies indicated that progesterone inhibited MMP-2 or MMP-9 expression in endometriotic cells, whereas other studies indicated that progesterone did not change the MMP-2 or MMP-9 expression [23,24]. It was also reported that the MMP-10 expression in the endometriotic tissues of ovarian endometriosis was significantly increased compared to the expression in eutopic endometrial tissues without endometriosis [25], and our present results demonstrated that dienogest directly inhibited the MMP-10 expression in the endometriotic stromal cells. Taken together, the previous and present findings indicate that the suppression of MMP-10 expression (as well as those of MMP-1 and MMP-3) by dienogest might be one of dienogest's direct anti-endometriotic effects.…”
Section: Discussionmentioning
confidence: 99%